Modification of selective electrode based on magnetic molecularly imprinted polymer for bisphenol A determination - Piyawan Leepheng; Dalawan Limthin; Korakot Onlaor; Benchapol Tunhoo; Darinee Phromyothin; Thutiyaporn Thiwawong (Japanese Journal of Applied Physics, 2021)
Abstract Selective electrodes were modified by using the magnetic molecularly imprinted polymer (MMIP) technique on a screen-printed electrode (SPE) to detect bisphenol A (BPA). Superparamagnetic iron oxide nanoparticles (SPIONs) greatly enhance electrochemical signals due to their superparamagnetic properties. The SPIONs are non-toxic, biocompatible and highly stable. The SPIONs, especially magnetite (Fe 3 O 4 ), were synthesized from ferrous chloride and ferric chloride using a chemical co-precipitation method. The crystalline structure of the synthesized SPIONs was obtained by X-ray diffractometer, representing cubic inverse spinel structure like magnetite. The synthesized SPIONs had particle sizes of 9.87 ± 2.67 nm, which was confirmed by transmission electron microscope. The magnetic property was measured by a vibrating sample magnetometer, which presented the saturated magnetization, magnetic remanence value and coercivity as 48.76 emu g −1 , 0.497 emu g −1 and 6.265 Oe, respectively. The surfaces of modified electrodes were characterized by a scanning electron microscope, which revealed BPA template cavities on the electrode surface. The electrochemical properties were studied by cyclic voltammetry and amperometry. The bisphenol A-magnetic molecularly imprinted polymer electrode (BPA-MMIP/SPE) has a sensitivity of 2.909 with a limit of detection of 2.053 × 10 −8 M. The concentration range for BPA detection is 2.5 × 10 −8 to 1.00 × 10 −4 M, which can be applied to detection in a real sample.
Keywords: Analytical chemistry methods development; Electrochemical Analysis and Applications; Analytical Chemistry and Sensors